The Eastern question in 1812–1842 - Minasyan, Edik G.; Tunyan, Valery G.; Menkouski, Viachaslau I.; Hovhannisyan, Meri V.; Minasyan, Arevik E. (Journal of the Belarusian State University. History, 2025)
In the first half of the 19th century, there was an intensification of the Eastern question, which affected the interests of European powers. In this context, the position of the Russian Empire regarding the security of the Ottoman Empire’s territories was significant. The relations between the empires from 1812 to 1842 were situational in nature, as reflected in a number of treaties. A distinctive feature of the Treaty of Bucharest, signed in 1812, was Turkey’s observance of situational neutrality in order to await the outcome of Napoleon’s campaign against Russia. The Treaty of Adrianople was concluded in 1829 to resolve the Greek question and achieve a number of advantages, such as ensuring the security of the Transcaucasian territories and preserving the integrity of the Ottoman Empire. The rapprochement between Russia and Turkey stimulated the signing of the defensive alliance Treaty of Unkiar Skelessi in 1833, which affected the interests of Western countries. Despite Russia’s moderation in demands, the desire to preserve the Ottoman Empire and prevent the creation of a new imperial entity in the Middle East, the states failed to achieve full cooperation. England had a decisive influence on the nature of Russian-Turkish relations. For this reason, the Eastern question became a subject of political bargaining, a tool for obtaining various prerogatives and conducting expansionist policies by the Western powers. This approach delayed the resolution of the Eastern question, which exacerbated international relations but, up to a certain point, supported the already weakened Ottoman Empire. According to the conventions concluded in London in 1840–1841, the Treaty of Unkiar Skelessi was annulled, and the Black Sea straits of the Bosphorus and Dardanelles came under the control of European states.
Keywords: Eastern question; interests; great powers; Black Sea straits; modernisation; interstate relations